2016
DOI: 10.3390/jcm5030035
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function as a Determinant of HDL and Triglyceride Concentrations in the Australian Population

Abstract: Background: Chronic kidney disease (CKD) is a potent risk factor for cardiovascular disease (CVD). CVD risk increases in a stepwise manner with increasing kidney impairment and is significantly reduced by kidney transplantation, suggesting a causal relationship. Dyslipidemia, a well recognised CVD risk factor, is highly prevalent in CKD. While dyslipidemia is a risk factor for CKD, kidney impairment can also induce a dyslipidemic state that may contribute to the excess burden of CVD in CKD. We utilised a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…In addition, eGFR was observed to correlate inversely with hyper-LDL-cholesterolemia in the control subjects. These results were consistent with a previous report (25), showing a causal association with early and advanced stages of renal dysfunction.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, eGFR was observed to correlate inversely with hyper-LDL-cholesterolemia in the control subjects. These results were consistent with a previous report (25), showing a causal association with early and advanced stages of renal dysfunction.…”
Section: Discussionsupporting
confidence: 83%
“…This impaired HDL-cholesterol metabolism in CKD leads to the accumulation of immature HDL particle precursors with limited anti-oxidative and anti-inflammatory potential 34,[50][51][52] . Renal transplant recipients often have high levels of HDL-cholesterol but are not protected against atherogenesis, probably as a direct result of the reduced quality of these HDL particles 13,53 .…”
Section: [H2] Reverse Cholesterol Transportmentioning
confidence: 99%
“…In kidney transplant patients, the restoration of kidney function results in a significant increase in HDL (p < 0.0001); however, if the graft function is not maintained, HDL level reduction is observed (p < 0.01) [77]. In turn, Kopecky et al [78] demonstrated that HDL from renal transplant recipients had strikingly altered molecular composition, mainly the enrichment in two proteins (SAA and SP-B), and it exerted impaired biological functions.…”
Section: Kidney Transplantationmentioning
confidence: 99%